Analysis of NMT Users on Social, Economic and Cultural Characteristics Relating to Transport Mode System Integration - Evi Puspitasari,; Fajar Susilowati,; Desty Aviani, (Recent Trends in Civil Engineering and Built Environment, 2025)
Walking and cycling, as non-motorized transportation (NMT), are expected to reduce transportation problems such as congestion and improve the quality of life. However, NMT has a lot of limitations such as low vehicle speed which causes time inefficiencies, low accessibility, and in-compatible with door-to-door travel. This research aims to discover the development of NMT in terms of its mode integration system and analyze the social, economic, and cultural aspects underpinning NMT's future growth. The method used in this study is analyzing conditions with tables and graphs with explanatory analysis. Based on the results, sidewalk damage occurred almost evenly in the pedestrian facilities. NMT facilities will be developed based on the number of pedestrians and additional width required based on the land use. The study of the mode integration system is based on the results of the transit point survey, it is planned that there will be an addition of stops on the roads reviewed. Economic, social, and cultural aspects show a positive perspective on existing conditions.